Poverty, participation, and democracy a global perspective - Krishna, Anirudh 1958- (Cambridge University Press, 2008)
For too long a conventional wisdom has held sway, suggesting that poor people in poor countries are not supportive of democracy and that democracies will be sustained only after a certain average level of wealth has been achieved. Evidence from 24 diverse countries of Asia, Africa and Latin America examined in this volume shows how poor people do not value democracy any less than their richer counterparts. Their faith in democracy is as high as that of other citizens, and they participate in democratic activities as much as their richer counterparts. Democracy is not likely to be unstable or unwelcome simply because poverty is widespread. Political attitudes and participation levels are unaffected by relative wealth. Education, rather than income or wealth, makes for more committed and engaged democratic citizens. Investments in education will make a critical difference for stabilizing and strengthening democracy